2017
DOI: 10.1161/circheartfailure.116.003804
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Cardiac Galectin-3 in Patients With Heart Failure Reflects Both Inflammation and Fibrosis

Abstract: Background— Galectin (Gal)-3 is a β-galactoside-binding lectin and currently intensely studied as a biomarker in heart failure. Gal-3 also exerts proinflammatory effects, at least in extracardiac tissues. Objective of this study was to characterize the relationship of plasma and myocardial Gal-3 levels with cardiac fibrosis and inflammation in patients with nonischemic dilated cardiomyopathy and inflammatory cardiomyopathy (iCMP). Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 37 publications
2
58
0
5
Order By: Relevance
“…In some clinical studies, Gal-3 plasma levels were not directly related to specific cardiac parameters of HF, including echocardiographic parameters [59]. Moreover, a study in which endomyocardial biopsies were taken from dilated and inflammatory cardiomyopathy patients revealed that Gal-3 levels in these biopsies did not reflect plasma Gal-3 levels [60]. Finally, in HF patients with elevated Gal-3 plasma levels prior to heart transplantation, the levels did not decline post-transplantation, which indicated that other non-cardiac sources were predominantly responsible for elevated Gal-3 plasma levels in these patients [61].…”
Section: Fibrosis Marker Gal-3mentioning
confidence: 99%
“…In some clinical studies, Gal-3 plasma levels were not directly related to specific cardiac parameters of HF, including echocardiographic parameters [59]. Moreover, a study in which endomyocardial biopsies were taken from dilated and inflammatory cardiomyopathy patients revealed that Gal-3 levels in these biopsies did not reflect plasma Gal-3 levels [60]. Finally, in HF patients with elevated Gal-3 plasma levels prior to heart transplantation, the levels did not decline post-transplantation, which indicated that other non-cardiac sources were predominantly responsible for elevated Gal-3 plasma levels in these patients [61].…”
Section: Fibrosis Marker Gal-3mentioning
confidence: 99%
“…In patients with inflammatory cardiomyopathy (iCMP) and nonischemic dilated cardiomyopathy, the level of myocardial Gal-3, but not circulating concentrations of Gal-3, was found as a possible marker for cardiac fibrosis, depending on pathogenesis of heart failure [23]. In the study of 259 blood samples and endomyocardial biopsies from heart failure patients, plasma myocardial mRNA and protein expression of Gal-3 were measured.…”
Section: Galectin-3mentioning
confidence: 99%
“…In patients with acute HF and acutely decompensated HF galectin-3 was associated with NTproBNP levels and the estimated glomerular filtration rate (GFR) but not with age and serum cardiac troponins (Besler et al, 2017). Nowadays galectin-3 is concerned the predictive biomarker for all-cause mortality, CV mortality and HFrelated clinical outcomes in patients with established HF.…”
Section: Galectin-3mentioning
confidence: 99%
“…Additionally, there is a huge list of the diseases associated with increased level of NPs beyond HF development ( Table 2). Although galectin-3 is an independent predictor of all-cause mortality, CV death and occurrence of HF, there is an inverse relationship between serum galectin-3 and estimated glomerular filtration rate (Besler et al, 2017). Accordingly, lowered kidney clearance should be taken into consideration, when data of galectin-3 measurement are interpreted.…”
Section: Limitations In Use Of Conventional Biomarkers In Hfmentioning
confidence: 99%